2021
DOI: 10.1038/s41380-021-01130-0
|View full text |Cite
|
Sign up to set email alerts
|

Associations of family income with cognition and brain structure in USA children: prevention implications

Abstract: Poverty, as assessed by several socioeconomic (SES) factors, has been linked to worse cognitive performance and reduced cortical brain volumes in children. However, the relative contributions of the various SES factors on brain development and the mediating effects between cognition and brain morphometry have not been investigated. Here we used cross-sectional data from the ABCD Study to evaluate associations among various SES and demographic factors, brain morphometrics, and cognition and their reproducibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
64
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 65 publications
7
64
1
1
Order By: Relevance
“…Recent ABCD studies have provided proof-of-concept for brain-behavior-environment analyses that map neural parameters to multiple exposures 75, 76 , and for the potential to use a subset of environmental risk factors to explain variance in mental health outcomes 77 . In addition, several studies have reported associations of specific exposures with cognition and neuroimaging parameters in ABCD data (e.g., household income 42 , neighborhood disadvantage 78 , lead exposure 41 ). The studies mentioned above all used baseline ABCD data, which does not include key environmental exposures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent ABCD studies have provided proof-of-concept for brain-behavior-environment analyses that map neural parameters to multiple exposures 75, 76 , and for the potential to use a subset of environmental risk factors to explain variance in mental health outcomes 77 . In addition, several studies have reported associations of specific exposures with cognition and neuroimaging parameters in ABCD data (e.g., household income 42 , neighborhood disadvantage 78 , lead exposure 41 ). The studies mentioned above all used baseline ABCD data, which does not include key environmental exposures.…”
Section: Discussionmentioning
confidence: 99%
“…For example, since parental factors play a major role in childhood development, we included parental psychopathology in our analyses, even though we acknowledge that genetic contributions of parental psychopathology also exist in the child. Furthermore, because we wanted to investigate the utility of applying an exposome framework, we excluded two pivotal measures commonly used to estimate environment, including in previous ABCD Study research: household income 40,41 and parental education 42 . This choice allowed us (1) to test the "added value" of the exposome scores to explain variance in health outcomes over and above commonly used proxies of environment known to associate with developmental outcomes 43 , including in ABCD Study 41 ; and (2) to validate the exposome scores using "classic" indicators of socioeconomic environment.…”
Section: Dimensionality Reduction Of the Exposome In Abcd Studymentioning
confidence: 99%
“…In a cross-sectional study examining 11,875 children aged 9 to 10 years old, Taylor et al found that neighborhood poverty was linked to differences in the volume of prefrontal and hippocampal areas, and also affected performance on cognitive tests (R. L. Taylor, Cooper, Jackson, & Barch, 2020) (Amso, 2020). Tomasi and Volkow found cognitive family SES and health behavior variables significantly correlates with family income, cortical volume, and cortical thickness, suggesting that the lack of emotional and educational support/education children from low-income families might experience may result in reduced cortical volume and cortical thickness (Tomasi & Volkow, 2021). Interestingly, Krogsrud et al found cortex thickness was not mediated by genetics nor socioeconomic status (Krogsrud et al, 2021).…”
Section: Ses Influences On Brain Developmentmentioning
confidence: 99%
“…Measurement of childhood SES is complex, and the most common indicators are family income, parental education, and parental occupation (McLoyd, 1998). Some scientists have just investigated the association between SES measures and brain development recently (Judd et al, 2020;Noble and Giebler, 2020;Tomasi and Volkow, 2021). Typical results include that: (i) Children from low income families may have a lower frontal, temporal, and hippocampal volume, as well as smaller brain surface area; (ii) Children from family with low parental education may have a lower cortical thickness in frontal areas; and (iii) Higher parental education level may be associated with significantly increased volume in the fetal white matter, deep gray matter, and brainstem.…”
Section: Introductionmentioning
confidence: 99%